"Garnishing" the photosynthetic bacterial reaction center for bioelectronics. Issue 25 (7th July 2015) - Operamolla, Alessandra; Ragni, Roberta; Milano, Francesco; Roberto Tangorra, R.; Antonucci, Alessandra; Agostiano, Angela; Trotta, Massimo; Farinola, Gianluca
<x xml:space="preserve">Abstract</x> Chemical manipulations of the photosynthetic bacterial reaction center for the implementation of this photoenzyme into bioelectronic devices are overviewed.